A Historical View of the Hindu Astronomy : From the Earliest Dawn of that Science in India to the Present Time - Bentley, John (Place of publication not identified : publisher not identified, 1825)
Shrouded in poetry, the earliest accounts of Hindu astronomy can strike modern readers as obscure. They involve the marriage of the moon to twenty-seven princesses, a war between gods and giants, and shadows that give birth to planets. In this fascinating study, first published in Calcutta in 1823 and reissued here in the 1825 edition, John Bentley (c.1750-1824) strives to strip back the mythical aspects of the stories to reveal their foundations. He points out that early Hindu astronomers divided the night sky into twenty-seven sections; that a solar eclipse could have been described as an epic war between light and dark; and that Saturn is often observed in the Earth's shadow. Using data from modern astronomical tables, he dates events, texts and people, whether mythical or factual, as well as charting the history of Indian astronomy from its earliest records to its modern developments.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).